Effect of the spatial resolution of digital terrain data obtained by drone on urban fluvial flood modeling of mountainous regions - X. Zhou; X. Zhou; L. Mou; T. Ao; T. Ao; X. Huang; X. Huang; H. Yang; H. Yang (Hydrology and Earth System Sciences)
Analysis of the effect of the resolution and quality of terrain data, as the most sensitive input to 2D hydrodynamic modeling, has been one of the main research areas in flood modeling. However, previous studies have lacked discussion on (1) the limitations of the target area and the data source and (2) the underlying causes of simulation bias due to different resolutions. This study first discusses the performance of a high-resolution digital terrain model (DTM), acquired using a drone, for flood modeling in a mountainous riverine city; analyses the effect of the DTM resolution on the results using grid resolutions from 6 cm to 30 m; and then investigates the root causes of the effect based on topographic attributes. Xuanhan, a riverine city in the mountainous region of Southwestern China, was used as the study area. The Hydrologic Engineering Center's River Analysis System (HEC-RAS) 2D model was used for all simulations, and the results generated using a 6 cm DTM acquired by drone were used as a benchmark. The results indicate that flood characteristic simulations exhibit noticeable stepwise changes as the DTM resolution varies. DTMs with a resolution better than 10 m are more effective with respect to capturing the terrain's undulating features in the study area, which is crucial for accurately modeling the inundation area. However, to accurately capture topographic features related to elevation differences, the resolution should preferably be better than 5 m, as this directly affects the accuracy of flood depth simulation. The analysis of topographic attributes provides theoretical support for determining the optimal resolution to meet simulation requirements.